Protocol for a study to evaluate the safety and efficacy of prophylactic negative pressure wound therapy after abdominal perineal resection (VACPAC study) - Takuya Takami; Yoshiro Itatani; Yu Yoshida; Nobuaki Hoshino; Ryo Ohno; Ryosuke Okamura; Koya Hida; Kazutaka Obama (PLoS ONE, 2025)
Introduction Abdominal perineal resection (APR) is a surgical procedure for rectal cancer that frequently results in perineal wound surgical site infections (SSI), particularly in high-risk patients undergoing preoperative treatment. SSI after APR is associated with prolonged hospital stay, increased medical costs, and delayed initiation of adjuvant chemotherapy, potentially leading to poor prognosis. Although omentoplasty and myocutaneous flap reconstruction have been used to prevent SSI, they are not always feasible. Prophylactic negative pressure wound therapy (pNPWT) has been shown to reduce SSI in high-risk wounds; however, its efficacy in APR remains unclear. This study aims to evaluate the safety and efficacy of pNPWT in preventing perineal wound SSI after APR. Methods and materials This is a multi-institutional, single-arm trial investigating pNPWT after APR. The study includes patients undergoing APR for malignant rectal tumors who meet the high-risk criteria for SSI. The intervention involves applying the 3M™ Prevena™ Plus Customizable system immediately after perineal skin closure, maintaining pNPWT for up to 7 days. The primary endpoint is the incidence of perineal wound SSI within 30 days. Secondary endpoints include postoperative complications (Clavien–Dindo Grade III or higher), hospital stay, and completion proportion of pNPWT. Discussion This study seeks to provide clinical evidence of the efficacy of pNPWT in reducing perineal wound SSI after APR. Given its ease of application and minimal invasiveness, pNPWT may serve as an effective approach for SSI prevention. These findings may contribute to the establishment of a standardized preventive approach for perineal wound management after APR.